2021
DOI: 10.15414/jmbfs.4764
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic, Cadmium and Mercury in the Macrolepiota Procera (Scop.) Singer Fruiting Bodies

Abstract: mushroom samples exceeded EU limits, and as such, they can pose a risk to human health. ARTICLE INFO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The average Hg content detected in Leccinum scabrum was 1.41 (0.674–2.94) mg kg −1 DW. Jančo et al [ 41 , 49 ] also confirmed the significant effect of the locality on the total Hg content in edible parts of mushrooms. Some previous studies showed that Macrolepiota procera collected from Central Slovakia (Banská Bystrica) had an average Hg concentration of 1.98 mg kg −1 (from 0.41 to 3.20 mg kg −1 ) in the caps and 1.40 mg kg −1 (from 0.12 to 1.75 mg kg −1 ) in stems.…”
Section: Resultsmentioning
confidence: 86%
“…The average Hg content detected in Leccinum scabrum was 1.41 (0.674–2.94) mg kg −1 DW. Jančo et al [ 41 , 49 ] also confirmed the significant effect of the locality on the total Hg content in edible parts of mushrooms. Some previous studies showed that Macrolepiota procera collected from Central Slovakia (Banská Bystrica) had an average Hg concentration of 1.98 mg kg −1 (from 0.41 to 3.20 mg kg −1 ) in the caps and 1.40 mg kg −1 (from 0.12 to 1.75 mg kg −1 ) in stems.…”
Section: Resultsmentioning
confidence: 86%